ANALISIS PENGENDALIAN KUALITAS UNTUK MENURUNKAN CACAT PRODUK KAOS JERSEY DENGAN METODE SIX SIGMA DAN RCA DI KONVEKSI X - Supmana, Serly; Prasetyo, Rian; Sari, Maria Puspita (Teknik Industri Unikom, 2024)
Quality control is an important aspect in increasing the efficiency and reliability of production processes in business. This research was conducted at industry X in the textile industry. This research examines t-shirt products because they are the best seller products. In the t-shirt production process at this convection, there is a percentage of product defects in jersey t-shirts of 6.22% which exceeds the convection target. This problem can be detrimental to the convection. The aim of this research is to reduce defects in t-shirt products using the six sigma and RCA methods, with this method it can reduce defects to close to zero defects. Based on research results on jersey t-shirts, there are 4 types of defects and the most dominant ones that cause defects on t-shirts are screen printing, 3 types of defects. Result 4 Fishbone Diagram of the main factors that cause defects in t-shirt products, namely, human factors, machines, materials and methods. In conclusion, from the 4 factors that cause defects in t-shirts, the proposed improvements are implemented, namely, providing understanding, warning and giving rest time to operators, checking raw materials at the beginning before entering the warehouse and using them, carrying out machine maintenance and using the right machine settings, implementing SOPs. work, and stricter QC supervision. Based on the results of the implementation of the proposed improvement, this research succeeded in reducing defects. Before repairing jersey t-shirt defects, the percentage was 6.22% to 0.91% with a reduction difference of 5.31%. This reduction has reached the convection target, which targets 0-5% product defects on t-shirts